A study on the improvement of socioeconomic and educational status of families through various governmental schemes - Bagheri, Masoumeh et al. (2007)
Poor women lack the capital required for enterprise start-ups and although lending mechanisms exist in their economy, mainstream financial institutions are not oriented towards providing them with the funding they require. However, Non-governmental Organizations (NGO's) in India have promoted microfinance through women's self-help groups. This paper takes a look at a non-governmental organization operating in six villages with six self-help groups formed by BPL women in Khed block in the district of Pune. The results showed that self-help groups have a positive impact on the socioeconomic development of beneficiaries, and helped to improving decision making, marketing and communication skills, building self-confidence among beneficiaries through schemes meant for them. - Reproduced.
Keywords: Womens status; Social status